Natural Disasters and the Urban Poor - Fay, Marianne (World Bank, Washington, DC, 2012)
Natural disasters made two and a half million people homeless in Latin America between 1990 and 1999. The region has been plagued with an average of 30 disasters causing 7,500 fatalities a year for 30 years. Worse, the frequency of natural disasters appears to be rising. It is generally agreed that rapid population growth leading to larger and denser human settlements, combined with environment degradation are key reasons. The emergence of megacities, population concentration in coastal areas (which are particularly vulnerable), and persistent widespread poverty compound the problem.